Emerging drugs for bronchiectasis: an update. (June 2015) - Chang, Anne B; Marsh, Robyn L; Smith-Vaughan, Heidi C; Hoffman, Lucas R
<x xml:space="preserve">Abstract</x> Introduction: Recent research has confirmed the increasing burden of bronchiectasis, in affluent and developing countries. Bronchiectasis, the destruction and dilation of airways, is due to a variety of causes and is characterised by a self-perpetuating cycle of airway inflammation, infection and obstruction that results in substantial morbidity and mortality. Improved therapies that address these three components, and the diseases that both cause and result from bronchiectasis are required. Areas covered: In this review, we update our previous summary of the clinical features, pathophysiology and epidemiology of bronchiectasis among adults and children, highlighting the most recent advances in therapeutics. We discuss current treatment strategies and then identify key goals for future research on the causes and treatments of a variety of types of bronchiectasis. Expert opinion: Bronchiectasis remains an orphan disease with respect to the development of new therapies. There has been progress in the recognition and studies but further research is now required on the pathogenesis, prevention, and treatment of bronchiectasis in order to decrease its high burden. Such advances will require a concerted, global effort to coordinate studies of both the pathophysiology and potential treatments of this heterogeneous, chronic disease that affects people of all ages and demographics.